By law of conservation of momentum, m1u1 + m2u2 = m1v1 + m2v2 => m1u1 – m1v1 = m2v2 – m2u2 => m1 (u1 – v1) = m2 (v2 – u2)....eqn (1).
Now, for the two bodies, if m1 = m2 = m, u1 = u2 = u, and v1 = v2 = v, then from eqn(1), m (u–v) = m (v–u).
=> u–v = v–u => u–v = {(v–u)/t} × t
( multiplying and dividing RHS with t).
=> u–v = at => u = v + at.... eqn(2).
But, eqn(2) contradicts the 1st equation of motion, according to which, v = u + at.
Which is correct then? The 1st equation of motion, or eqn(2) given above?
Answers
Answered by
0
Answer:
good morning have a nice day
Answered by
0
Answer:
- here is the answer
Explanation:
- please mark as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/d2c/6202e2fbead96c8e3dba066c615c08c3.jpg)
Similar questions